KNOWLEDGE AND ATTITUDE OF FARMERS TOWARDS ANTIMICROBIAL RESISTANCE IN ASIA: A SYSTEMATIC REVIEW AND META-ANALYSIS: Pengetahuan dan Sikap Peternak terhadap Resistensi Antimikroba di Asia: Tinjauan Sistematis dan Meta-Analisis - Muhammad Mikail Athif Zhafir Asyura; Novia Angela (Jurnal Berkala Epidemiologi, 2023)
Background: Antimicrobial resistance is a severe threat to public and environmental health. The agricultural sector contributes significantly to resistance, where antimicrobials are used as prophylaxis, growth promoters, and for treatment. A series of studies have been conducted to assess farmers' knowledge and attitude levels with varying results, particularly in Asia, one of the world's largest producers of livestock products. Purpose: To review the pooled estimated level of knowledge and attitude towards antimicrobial use and resistance in Asia. Methods: A literature search was conducted according to PRISMA in Scopus, PubMed, Google Scholar, and Embase for studies up to 30 April 2023. Quality was assessed using the Newcastle-Ottawa Scale (NOS) for cross-sectional studies. Outcomes were further categorized into constructs under knowledge and attitude. Random-effect meta-analysis was conducted using STATA 17. Results: 11 studies and 2131 subjects were included with fair to excellent quality. From the meta-analysis, the following knowledge and attitude levels were estimated: definition [55.7% (95%CI: 37.3%-74%)] and cause [60.6% (95%CI: 40.5%-80.6%)] of antimicrobial resistance; the negative impact of antimicrobials [62.6% (95%CI: 16.9%-100.0%)]; use of antimicrobials for treatment [47.8% (95%CI: 6.1%-89. 4%)], prophylaxis [58.5% (95%CI: 28.5%-88.5%)], growth promoter [39% (95%CI: 23.1%-54.9%)]; discontinuation of antimicrobials upon improving conditions [42.5% (95%CI: 15.4%-69.5%)]. Conclusions: Farmers in Asia have moderate knowledge of antimicrobial resistance but still exhibit attitudes that support resistance.